A study of macroeconomic variables that effects Shariah Index in India / Muhammad Hafizuddin Rokman - Rokman, Muhammad Hafizuddin (Faculty of Business and Management, 2011)
Shariah Index is a type of index that consist of stocks that are Shariah-compliant. It means that the stock is from company that follow the Islamic law which is Shariah law. It includes in prohibition of non-halal product such as pork and tobacco and also non-halal activities such as gambling. This study tries to discover the relationship between interest rates, exchange rates and inflation rates with Shariah Index in India which is FTSE Shariah India Index. Multiple Linear Regression model is applied on the monthly data of those macroeconomic variables and Shariah index for three years period which is from January 2008 to December 2010. The results shows that all the macroeconomic variables has significant effect with the Shariah index in India. In addition, the findings also shows that only inflation rates has positive relationship on the Shariah Index in India while the other two has negative relationship.